PERAN GURU PENDIDIKAN AGAMA KRISTEN SEBAGAI PEMBIMBING DALAM PEMBENTUKAN KARAKTER SISWA - Juwinner Dedy Kasingku; Faldo Nun Sasarari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article discusses how the role of Christian religious education teachers as mentors at SMP Advent Waropen to build the students' characters. The research design used was a qualitative research method for 6 students in grades 8 and 9. The researcher has 7 questions and modified them so that the questions could describe the questions selected from the research. The research outcomes indicated that the role of Adventist Christian teachers at SMP Advent Waropen influenced significantly the students’ character building. Therefore, Christian religious education mentors needed to be capable of guiding the students at Junior High School Advent Waropen and had positive traits like self-control, integrity, excellent character, and politeness. The researcher also found that there was cooperation between teachers, parents, and the communities in developing students’ character. The role of Christian religious education teachers as mentors at SMP Advent Waropen was very important for students. And with the cooperation used by teachers, parents, and the communities, the process could be gradually applied and implemented.